Molecular magnetic resonance imaging of Alpha-v-Beta-3 integrin expression in tumors with ultrasound microbubbles. (August 2021) - Pathak, Vertika; Nolte, Teresa; Rama, Elena; Rix, Anne; Dadfar, Seyed Mohammadali; Paefgen, Vera; Banala, Srinivas; Buhl, Eva Miriam; Weiler, Marek; Schulz, Volkmar; Lammers, Twan; Kiessling, Fabian
Abstract: Microbubbles (MB) are used as ultrasound (US) contrast agents and can be efficiently targeted against markers of angiogenesis and inflammation. Due to their gas core, MB locally alter susceptibilities in magnetic resonance imaging (MRI), but unfortunately, the resulting contrast is low and not sufficient to generate powerful molecular MRI probes. Therefore, we investigated whether a potent molecular MR agent can be generated by encapsulating superparamagnetic iron oxide nanoparticles (SPION) in the polymeric shell of poly (n-butylcyanoacrylate) (PBCA) MB and targeted them against αv β3 integrins on the angiogenic vasculature of 4T1 murine breast carcinomas. SPION-MB consist of an air core and a multi-layered polymeric shell enabling efficient entrapment of SPION. The mean size of SPION-MB was 1.61 ± 0.32 μm. Biotin-streptavidin coupling was employed to functionalize the SPION-MB with cyclic RGDfK (Arg-Gly-Asp) and RADfK (Arg-Ala-Asp) peptides. Cells incubated with RGD-SPION-MB showed enhanced transverse relaxation rates compared with SPION-MB and blocking αv β3 integrin receptors with excess free cRGDfK significantly reduced RGD-SPION-MB binding. Due to the fast binding of RGD-SPION-MB in vivo, dynamic susceptibility contrast MRI was employed to track their retention in tumors in real-time. Higher retention of RGD-SPION-MB was observed compared with SPION-MB and RAD-SPION-MB. To corroborate our MRI results, molecular US was performed the following day using the destruction-replenishment method. Both imaging modalities consistently indicated higher retention of RGD-SPION-MB in angiogenic vessels compared with SPION-MB and RAD-SPION-MB. Competitive blocking experiments in mice further confirmed that the binding of RGD-SPION-MB to αv β3 integrin receptors is specific. Overall, this study demonstrates that RGD-SPION-MB can be employed as molecular MR/US contrast agents and are capable of assessing the αv β3 integrin expression in the neovasculature of malignant tumors. Graphical abstract: Multimodal polymer-based microbubbles, encapsulating superparamagnetic iron oxide nanoparticles (SPION) in the shell and air in the core, were decorated with RGD peptides to enable molecular MRI and molecular US imaging of tumor angiogenesis in 4T1 tumors in mice. Upon intravenous administration, non-targeted control microbubbles did not show any binding to the tumor neovasculature. Conversely, RGD-targeted microbubbles showed high binding and prolonged retention, as assessed by dynamic susceptibility contrast MRI and contrast-enhanced US. Image 1